Selection of cemented carbide turning tools using EMF and optimization criteria - Amin, A. K. M. Nurul; Sarker, Md. Ruhul Amin; Ahmed, Mahiuddin; Karim, A.N. Mustafizul (Elsevier, 1998)
Tool life and quality of surface finish of the workpiece influence production rate and production cost. Cemented carbide tools have found wide application in the production arena of Bangladesh. In the absence of any testing facility in the country for the selection of cost-effective tools, poor quality carbide tools are frequently imported. A testing method and a selection criteria were developed for testing carbide tools of different shapes and sizes and for selecting the most cost-effective tool. For each tool cutting tests were performed to generate tool life data under different cutting conditions. Mild steel served as the work material. The relationship between tool life and cutting speed was developed using a curve-fitting software on a PC. From these relationships the values of the constants of the Taylor’s equation were determined. The cost equation was then derived for each tool for a given amount of work in a cutting speed range. Finally, the most cost-effective tool was selected on the basis of the relative location of the cost curves of the tools tested.